United Kingdom : Financial Sector Assessment Program-Stress Testing the Banking Sector-Technical Note. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses how Financial Sector Assessment Program (FSAP) stress test assesses the resilience of the banking sector as a whole rather than the capital adequacy of individual institutions. The FSAP approach to stress testing is essentially macroprudential: it focuses on resilience of the broader financial system to adverse macro-financial conditions rather than on resilience of individual banks to specific shocks. This test ensures consistency in macroeconomic scenarios and metrics across firms to facilitate the assessment of the banking system as a whole. The stress test analysis is intended to help country authorities to identify key sources of systemic risk in the banking sector and inform macroprudential policies to enhance its resilience to absorb shocks.